'AlkarXL', a new tall wheatgrass cultivar for use on saline semiarid lands. Issue 3 (27th June 2020) - Jensen, Kevin B.; Pearse, Gordon; Larson, Steve R.; Robins, Joseph G.
Abstract: The USDA announces the release of cultivar 'AlkarXL' (Reg. no. CV‐286, PI 691611) tall wheatgrass [ Thinopyrum ponticum (Podp.) Barkworth & D. R. Dewey] for use on semiarid rangelands and irrigated pastures that receive a minimum of 350 mm of average annual precipitation on alkali soils. AlkarXL is a 10‐clone synthetic that originated from 56 plant introductions from the National Plant Germplasm System plus the cultivar Alkar. AlkarXL has undergone phenotypic recurrent selection for visual plant vigor (first cycle), seed yield (first cycle), dry‐matter yield (DMY) (second cycle), and crude protein (second cycle). The 10 genotypes traced to PI 255146 (two genotypes; 30%, Turkey), PI 308592 (10%, Italy), PI 442631 (10%, Turkey), PI 109542 (10%, Turkey), PI 255443 (10%, Turkey), PI 383545 (10%, Turkey), PI 401006 (Turkey), PI 401009 (10%, Turkey), and W6 21870 (10%, Ukraine). Morphologically, AlkarXL has significantly wider lemmas and glumes and shorter glumes than cultivars Alkar, Greenstar, Jose, Largo, and Szarvasi‐1. AlkarXL had narrower flag leaves than Largo. AlkarXL had more seedlings ( P  < .05) emerge than Alkar at Lages Junction, NV. AlkarXL had greater ( P  < .05) plant persistence (plant frequency) 3 (2017), 4 (2018), and 5 (2019) yr after seeding at Lages Junction than did Alkar. Dry‐matter yield was less descriptive due to large variations in DMY among replications. AlkarXL had significantly ( P  < .10) more total DMY than Greenstar and Largo at Millville, UT, and similar DMY as Greenstar, Jose, and Savarsi‐1 at Panguitch, UT.